2011
DOI: 10.1007/s12088-011-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and Comparative Evaluation of a Competitive ELISA with Rose Bengal Test and a Commercial Indirect ELISA for Serological Diagnosis of Brucellosis

Abstract: The development of a competitive ELISA for the detection of brucella-specific antibodies in bovines is described. Anti-brucella guinea pig serum was used as a source of competing antibodies. Lipo-polysaccharide purified from inactivated B. abortus S19 culture was used as antigen for the development of the assay. Sera from cattle were used in the competitive ELISA, rose bengal test and a commercial indirect ELISA. The following cattle sera were tested: (i) known positive sera (n = 80) (ii) known negative sera (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…To further characterize the antibody reactions against various VP1 in Enterovirus genus, a competitive inhibition ELISA was conducted as described 37 38 39 . Briefly, the 96-well microtiter plates were coated with 1.0 μg of EV71 VP1 protein in 100 mM carbonate buffer (pH 9.6) overnight at 4 °C and then blocked for 2 h at 37 °C with 200 μl of 15% skimmed milk prepared in PBS-Tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…To further characterize the antibody reactions against various VP1 in Enterovirus genus, a competitive inhibition ELISA was conducted as described 37 38 39 . Briefly, the 96-well microtiter plates were coated with 1.0 μg of EV71 VP1 protein in 100 mM carbonate buffer (pH 9.6) overnight at 4 °C and then blocked for 2 h at 37 °C with 200 μl of 15% skimmed milk prepared in PBS-Tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the contribution of full length VP1 and various truncated VP1 proteins to the anti-EV71 VP1 reaction, the competitive inhibition ELISA was conducted as described 55 56 57 . Briefly, the 96-well microtiter plates was coated with 1.0 μg EV71 VP1 protein in 50 mM carbonate buffer (pH 9.6) overnight at 4 °C and then were blocked for 2 h at 37 °C with 200 μl of 15% skimmed milk prepared in PBS-Tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…Serological and molecular epidemiological studies can help in elucidating the genetic diversity and evolution of these pathogens [99]. It has also been observed that the studies included in the present meta-analysis commonly used techniques like biochemical tests and PCR [44,56,97] followed by ELISA [34,37,64] and lateral flow assays [33] for the detection of bacterial pathogens. It is very much desired that longitudinal studies are needed to monitor the changes in prevalence over time and to assess the effectiveness of control measures.…”
Section: Discussionmentioning
confidence: 99%